2018
DOI: 10.1002/jrs.5416
|View full text |Cite
|
Sign up to set email alerts
|

On‐site detection of succinylcholine in biomedical matrix by surface‐enhanced Raman spectroscopy

Abstract: Choline receptor blocker succinylcholine (suxamethonium [SUX]) is a depolarizing neuromuscular blocking agent to relax muscles. It is often used in clinic to conduct auxiliary endotracheal intubation as a surgical anesthetic inducer, which can cause respiratory depression and cardiac arrest. In recent years, SUX was occasionally used for theft and crime by daubing on darts, resulting in intoxication or even death. Regarding the rapid detection demand of SUX in first aid and emergency response, a bit of challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…MgI 2 , as the most effective aggregation agent to fentanyl, offered 20‐fold selectivity than NaCl aggregation system for fentanyl versus codeine (Fig. A), as well as provided lower baseline due to fluorescence quenching effect of I − . It benefited a better differentiation of trace fentanyl from heroin.…”
Section: Resultsmentioning
confidence: 99%
“…MgI 2 , as the most effective aggregation agent to fentanyl, offered 20‐fold selectivity than NaCl aggregation system for fentanyl versus codeine (Fig. A), as well as provided lower baseline due to fluorescence quenching effect of I − . It benefited a better differentiation of trace fentanyl from heroin.…”
Section: Resultsmentioning
confidence: 99%
“…The results demonstrate that SERS coupled with a flexible and absorbent SERS substrate can be used as a practical application for the reliable, rapid, and sensitive detection of pesticide residues . Wang and co‐workers described the on‐site detection of succinylcholine, a depolarizing neuromuscular blocking agent to relax muscles, in a biomedical matrix by SERS for the first time . Yan and co‐workers carried out a study of the thermal stability of ultrathin and high dielectric 1‐nm tetrahedral amorphous carbon films coated with Ag nanostructures for SERS detection .…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%
“…[53] Wang and co-workers described the on-site detection of succinylcholine, a depolarizing neuromuscular blocking agent to relax muscles, in a biomedical matrix by SERS for the first time. [54] Yan and co-workers carried out a study of the thermal stability of ultrathin and high dielectric 1-nm tetrahedral amorphous carbon films coated with Ag nanostructures for SERS detection. [55] Zengin et al reported on the SERS detection of polyaromatic hydrocarbons on β-cyclodextrin containing a polymer brush-coated silicon substrate and β-CD-SH modified gold NPs for the detection of polyaromatic hydrocarbons pyrene and anthracene.…”
Section: Sers Substratesmentioning
confidence: 99%
“…These two enhancement mechanisms have been involved in the ultrasensitive detection of molecules. Due to the sensitivity and selectivity of this technique, SERS has many applications in the field of analytical chemistry, biomolecules sensing, forensic science, homeland security, and clinical diagnosis …”
Section: Introductionmentioning
confidence: 99%